Pendampingan Produksi Bakso Higienis melalui Penerapan Sanitasi dan Keamanan Pangan Pada UMKM Dapur Sebelas Keamanan Pangan Pada UMKM Dapur Sebelas - Aneu Kuraesin RS; Yunia Mulyani Aziz (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (UMKM) in the food sector still face various challenges in implementing proper hygiene and sanitation practices during the production process. Dapur Sebelas, a meatball-producing UMKM in Bandung City, experienced several issues, including suboptimal cleanliness of the production area, inconsistent equipment sanitation, and the incomplete implementation of food safety practices. This community service program aimed to improve the knowledge, skills, and awareness of business owners regarding food safety, hygiene, and sanitation. The method employed was participatory assistance, consisting of initial observation, food safety counseling, training and demonstrations, implementation assistance, and evaluation. Evaluation was conducted through pre-tests and post-tests, field observations, and interviews. The results showed that the average participant score increased relatively by 41.94% (from 62 to 88). Furthermore, positive changes in production practices were observed, including improved workplace cleanliness, better equipment sanitation, routine implementation of food safety procedures, enhanced product quality, and increased consumer confidence in the products.